Measurements and modeling of the exsolution and dissolution kinetics of methane and bitumen system at T = (353.15–433.15 K). (15th July 2023) - Khan, Mansoor; Nath, Devjyoti; Hassanzadeh, Hassan
Graphical abstract: Abstract: We present the first experimentally measured data set on the exsolution/dissolution kinetics of methane and bitumen system at the test temperature range of 80–160 °C, and a pressure difference of 0.69 MPa, between 1.81 MPa and 2.5 MPa. An analytical model is used to estimate the exsolution and dissolution diffusion coefficients for the methane/bitumen system from the acquired data set. The results revealed faster exsolution kinetics compared to dissolution for the methane-bitumen system. The exsolution and dissolution diffusion coefficients were found to be in the range of (1.13–14.2) × 10 −8 m 2 /s and (1.95–56.9) × 10 −9 m 2 /s, respectively. Furthermore, the experimentally measured diffusivity measurements were modeled using the Arrhenius-type relationship, and the analysis indicated higher activation energy for the dissolution of methane in bitumen compared to the exsolution. The reported exsolution and dissolution diffusivity measurements have applications in the design and simulation of the solvent-assisted thermal recovery of bitumen and heavy oil.